Cities in time : temporary urbanism and the future of the city - Madanipour, Ali (London : Bloomsbury Academic, an imprint of Bloomsbury Publishing Pic, 2017)
'From street-markets and pop-up shops to art installations and Olympic parks, the temporary use of urban space is a growing international trend in architecture and urban design. Partly a response to economic and ecological crisis, it also claims to offer a critique of the status quo and an innovative way forward for the urban future. Cities in Time aims to explore and understand the phenomenon, offering a first critical and theoretical evaluation of temporary urbanism and its implications for the present and future of our cities. The book argues that temporary urbanism needs to be understood within the broader context of how different concepts of time are embedded in the city. In any urban place, multiple, discordant and diverse timeframes are at play - and the chapters here explore these different conceptions of temporality, their causes and their effects. Themes explored include how institutionalised time regulates everyday urban life, how technological and economic changes have accelerated the city's rhythms, our existential and personal senses of time, concepts of memory and identity, virtual spaces, ephemerality and permanence'--
Introduction: The multiple times of the city -- Instrumental temporality. Regulating time in everyday life -- Accelerated cities -- Existential temporality. Memory and identity in the city -- The phenomenology of anxiety -- Experimental temporality. Events and interventions-from pop-ups to Olympic parks -- Conclusion: Temporary urbanism as symptom, response, and catalyst.
Includes bibliographical references.
Keywords: Urbanization; Time -- Social aspects